Chemical Composition, Antioxidant and Antimicrobial Activities of Pimpinella enguezekensis : A Novel Species from Anatolia, Turkey- Fruit Essential Oil - Karik, Unal; Demirbolat, Ilker (My University, 2020)
Essential oil was obtained from Pimpinella enguezekensis, a novel species found in Eastern Anatolia, Turkey. The samples were collected in Agilbasi (Enguzek), Malatya, Turkey, where the new species was first discovered. The essential oil was isolated through hydro distillation and analyzed through GC/FID- MS. The average essential oil obtained was 3.7 %, and 21 compounds, accounting for 99.2 % of the essential oil, were identified. The major components of P. enguezekensis essential oil were trans-anethole (86.8 %), methyl chavicol (4.8 %), and pseudoisoeugenol 2-methylbutyrate (3.5 %). DPPH and beta-carotene/linoleic acid assays revealed that this essential oil had significant antioxidant activities. It also showed moderate antimicrobial activities against six bacterial and two yeast species. Its composition, antioxidant and antimicrobial properties were studied for the first time.